Vegetation patterns and hydro-geological drivers of freshwater rock pool communities in the monsoon-tropical Kimberley region, Western Australia - Cross, A.; Turner, S.; Merritt, D.; Van Niekerk, A.; Renton, M.; Dixon, Kingsley; Mucina, L. (Wiley-Blackwell, 2015)
Question Freshwater rock pools (FRP) are small, highly stressed wetland habitats that harbour many range-restricted and specialized plants. We examined the phytosociological patterns of FRP in a biodiverse monsoon-tropical region, to establish the influence of hydro-geological drivers on vegetation patterns in rock pool plant communities. Location Gardner Plateau, central North Kimberley, Western Australia (centre of the study area: 14°47′46″ S, 126°31′27″ E). Methods A total of 1066 phytosociological relevés (microplots), as well as measurements of physical habitat characteristics, were collected from 580 rock pools. Communities were classified using clustering and table sorting. The hydrological regime of each rock pool was dynamically modelled, and the most significant predicative hydro-geological factors were determined for each species and vegetation community using canonical correlation analysis, classification and regression trees and random forests. Results Variation in maximum rock pool depth, hydroperiod and the number of annual innundation events were identified as the most significant environmental predictors of community composition. All resident taxa were either regional or narrow-range endemics, with four species representing strict FRP specialists. FRP-specialist taxa exhibited the highest levels of hydro-geological specialization, and these species occurred in distinct communities characterized by longer periods of inundation and fewer annual inundation events than assemblages of non-specialist rock pool species. Eight distinct plant communities were recognized.Conclusions: FRP in the monsoonal tropics are dynamic and hydrologically unpredictable aquatic ecosystems that harbour a number of unique plant communities. The duration and periodicity of seasonal inundation represent major ecological drivers of vegetation assemblages in these habitats, with inhabitant species exhibiting a progression of specialization to hydro-geological factors along a gradient of hydrological stability. Although the colonization of individual rock pools by wetland plants appears to be a random process governed by the serendipity of seed arrival events, the comparative stability of FRP over long geological time frames may have facilitated the persistence of a small number of highly specialized taxa in these ecosystems.